2022
DOI: 10.3390/ph15070783
|View full text |Cite
|
Sign up to set email alerts
|

Biologics in COVID-19 So Far: Systematic Review

Abstract: This systematic review aimed to reevaluate the available evidence of the use of biologics as treatment candidates for the treatment of severe and advanced COVID-19 disease; what are the rationale for their use, which are the most studied, and what kind of efficacy measures are described? A search through Cochrane, Embase, Pubmed, Medline, medrxiv.org, and Google scholar was performed on the use of biologic interventions in COVID-19/SARS-CoV-2 infection, viral pneumonia, and sepsis, until 11 January 2022. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…Many other anti-inflammatory and anti-cytokine agents or inflammation-modulating biologics (Jones et al ., 2021; Arias et al ., 2022), such as anti-IL-1 agent Anakinra, have been tried in severe COVID. It is quoted that there are more than 150 clinical trials on biologic therapy for COVID-19 in progress (González-Gay et al ., 2021).…”
Section: Hypometabolism and Hypermetabolism In Brain Areas Revealed B...mentioning
confidence: 99%
“…Many other anti-inflammatory and anti-cytokine agents or inflammation-modulating biologics (Jones et al ., 2021; Arias et al ., 2022), such as anti-IL-1 agent Anakinra, have been tried in severe COVID. It is quoted that there are more than 150 clinical trials on biologic therapy for COVID-19 in progress (González-Gay et al ., 2021).…”
Section: Hypometabolism and Hypermetabolism In Brain Areas Revealed B...mentioning
confidence: 99%
“… 4 , 5 These efforts identified several potential therapeutics and resulted in some “hits” that have been of use, such as dexamethasone for ICU and ventilated patients, Paxlovid (orally active), and Remdesivir (iv infusion) antivirals for use in infected patients at risk of morbidity or death from severe infection. 6–8 Administration of convalescent plasma from recovered COVID-19 patients was also reported to prevent hospitalizations in a clinical trial of outpatients with recently confirmed SARS-CoV-2 infection. 9 Along those same lines, combination therapy with Bamlanivimab and Etesevimab monoclonal antibodies reduced viral load in patients with mild to moderate illness.…”
Section: Introductionmentioning
confidence: 98%
“… 2 Several studies have identified elevated levels of IL6 as it relates to SARS-CoV-2, thus making the anti-IL6 properties of tocilizumab favorable for treating severe illness. 2 , 3 Therefore, we theorize that asthmatics on biologics are at less risk of developing severe infections due to concurrent biologic treatment than those not on biologics.…”
Section: Introductionmentioning
confidence: 99%